Critical Analysis of Phonics Reading Approach Implementation for Very Young Learners in Non-Formal Education - Utami, Setyo; Subhan, Ulya Maulani; Maidah, Anik Nur; Shalihah, Imra’atus (Universitas Dian Nuswantoro, 2025)
The existing literature has documented the success of the phonics approach in teaching early reading in school contexts. Yet, research examining how teachers implement this approach, particularly in non-formal educational settings, remains limited. This qualitative case study aims to explore and critically analyze the application of phonics in a private language course in Jember, Indonesia, as well as the associated challenges. The study involved four teachers from the institution, and data were collected through observations, interviews, field notes, and document analysis. The findings suggest that phonics can help guide very young learners to develop their early literacy skills when applied explicitly and systematically. However, phonics itself can prove more complex than anticipated. Due to its technical nature and lack of support for meaning comprehension, phonics should not be the sole approach in a reading class. Therefore, it should be incorporated with meaning-based reading approaches and adequate teacher training to promote effective phonics instruction.